Rol' vozrastnoj geterochronii v krizisnych projavlenijach sportivnoj kar'ery - Timakova, T. S. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The problem of preservation the necessary balance of physical and psycho-emotional potential in representatives of high-performance sports at periods of biological development is considered. In sports with an early beginning of specialization, entry into professional sports coincides with the complicated processes of age maturation. Ignoring the individual peculiarity of biological development in the midst of active performances often provokes crisis manifestations in the sports career. This is especially true for highly gifted and tall athletes of complex phenotypic organization. The article provides concrete examples of some representatives of the swimming elite with different variants of heterochrony of development passage.